PEMANFAATAN MEDIA SOSIAL TWITTER SEBAGAI RUANG BERCERITA BAGI KORBAN PELECEHAN SEKSUAL - Rinaldi, Rasheesa Dwianatha Putri; Hermawati, Rina (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
The cases of sexual harassment increases every year and often happen to women. In 2017, there are 2,657 cases of violence against women in public spaces were recorded, including 911 cases of sexual abuse, 704 cases of sexual harassment, 699 cases of rape and 343 cases of sexual intercourse. According to gender experts, frequent sexual harassment has been seen as a form of male authority or domination over women. It has been proven that sexual harassment can occur anywhere, both in public places and on social media. Rapid technological developments can make it easier for women to use social media as a space to share experiences and spread education about sexual harassment to other users. Social media that gives women enough freedom to express themselves is Twitter. Victims who have experienced sexual harassment have the courage to share their stories and even distribute evidence of the harassment that occurred, through photos, videos, screenshots of conversations, or other concrete evidence. Therefore, this research will look at and analyze how women use the social media Twitter as a safe place to share their experiences as victims of sexual harassment through the uses and gratifications theory. The use of social media in telling stories about experiences of sexual harassment is determined by social norms that limit or support women from speaking out.